Eksplorasi Outdoor Learning dalam Mengembangkan Keterampilan Sains Siswa Sekolah Dasar - La Sisi; Chairan Zibar L. Parisu (FKIP UNSULTRA, 2025)
Outdoor learning is a learning approach that involves learning activities outside the classroom, providing students with direct experiences in a natural context. This article examines the role of outdoor learning in developing elementary school students' science skills through a literature study. Science learning conducted outside the classroom allows students to observe natural phenomena directly, which supports the understanding of science concepts in a more real and enjoyable way. Various studies have shown that outdoor learning can improve students' science skills, both in terms of conceptual understanding, experimental skills, and critical thinking skills. This method also supports the development of positive attitudes towards science and strengthens the connection between theory and practice. This article presents empirical evidence related to the impact of outdoor learning on elementary school students' science skills, as well as challenges and solutions in its implementation. The results of the study indicate that outdoor learning is effective in enriching learning experiences and providing a positive impact on students' science skills.